Analisis Serangan Hama Tikus Dan Monyet Pada Buah Kelapa Sawit di Perkebunan Rakyat Kabupaten Muaro Jambi - Wa’di, Khairul Shadiqul; Meilin, Araz; Nasamsir, Nasamsir (Universitas Batanghari, 2025)
Oil palm is a plantation crop that has good industrial prospects in the local and world markets. The productivity of oil palm plantations is often disrupted by the presence of plant pests or often called plant pests (opt). One of the pests that often poses a serious threat to oil palm fruit is attacks by mammalian pests such as rats and monkeys. This research was conducted in the oil palm plantations of the Suka Damai Farmers Group, Bukit Baling Village, Sekernan, Muaro Jambi and Mekar Sari Makmur Village, Sungai Bahar District, Muaro Jambi, Jambi using an unformatted trial research model. The results of the research showed that there were signs of rat and monkey attacks in the plantation area. The level of pest attacks in Bukit Baling Village with a percentage of rat attacks of 18.0% and monkey attacks of 10.00%. In Mekar Sari Makmur Village, the rat pest attack rate is 16.00% and the monkey pest attack rate is 4.44%. The intensity of rat and monkey pest attacks at the Bukit Baling location was 5.72% (light) and monkey pest attack intensity was 3.96% (very light). At the Mekar Sari Makmur location, the rat pest attack rate was 4.18% (very light) and the monkey pest attack rate was 0.88% (very light).